Incorporating the Influence of Walkability into a Model of Pedestrian Accessibility. - Jonietz, David; Timpf, Sabine (My University, 2013)
Representing a critical factor for maintaining the economic, cultural and social functionality of City centres, accessibility has traditionally been a central concept in urban transportation planning. However, when modeling urban accessibility, approaches have generally concentrated on motorized means of transportation, neglecting the fact that non-motorized modes, especially walking, play an essential role in urban settings. Moreover, it is acknowledged that pedestrians place specific demands on their environment, which are not restricted to distance, time or financial cost. Thus, this study presents an alternative GIS-based approach to model urban walking accessibility by integrating a walkability-index as an additional cost value, using the example of pedestrians in the main shopping district in the City centre of Augsburg.
Keywords: Verkehrsplanung; Stadtverkehr; Fußgängerverkehr; Verkehrsverhalten; Innenstadtverkehr; Empirische Untersuchung; GIS